2021
DOI: 10.1136/neurintsurg-2021-017859
|View full text |Cite
|
Sign up to set email alerts
|

Primary results of the Vesalio NeVa VS for the Treatment of Symptomatic Cerebral Vasospasm following Aneurysm Subarachnoid Hemorrhage (VITAL) Study

Abstract: BackgroundCerebral vasospasm (CV) after aneurysmal subarachnoid hemorrhage (aSAH) is linked to worse neurological outcomes. The NeVa VS is a novel cerebral dilation device based on predicate stent retrievers. We report the results of the Vesalio NeVa VS for the Treatment of Symptomatic Cerebral Vasospasm following aSAH (VITAL) Study.MethodsThis was a single-arm prospective multicenter trial to assess the safety and probable benefit of the NeVa VS device to treat CV. Patients were screened and treated if they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Crystalloid infusions to maintain euvolemia have been supported in the literature. 362 With euvolemia as part of goal-directed therapy, DCI was observed in 13% of the patients in the goal-directed therapy group and in 32% of the patients in the control group (odds ratio, 0.324 [95% CI, 0.11–0.86]; P =0.021) in 1 study. 245 Duangthongphon and colleagues 320 found that initiation of the euvolemic protocol reduced DCI from 44.2% to 7.7% (odds ratio, 0.10 [95% CI, 0.04–0.23]; P <0.001).…”
Section: 3 Management Of Cerebral Vasospasm and DCI After Asahmentioning
confidence: 91%
“…Crystalloid infusions to maintain euvolemia have been supported in the literature. 362 With euvolemia as part of goal-directed therapy, DCI was observed in 13% of the patients in the goal-directed therapy group and in 32% of the patients in the control group (odds ratio, 0.324 [95% CI, 0.11–0.86]; P =0.021) in 1 study. 245 Duangthongphon and colleagues 320 found that initiation of the euvolemic protocol reduced DCI from 44.2% to 7.7% (odds ratio, 0.10 [95% CI, 0.04–0.23]; P <0.001).…”
Section: 3 Management Of Cerebral Vasospasm and DCI After Asahmentioning
confidence: 91%
“…Instead, a mechanical radial force is gradually exerted on the spastic vascular wall by means of self-expansion after release of the stent retriever without the need for temporary occlusion. In addition, different novel non-occlusive stents are currently used for treating spasms [71][72][73]. In our institution we have had positive experiences with the Comaneci instrument with an adjustable and easy-to-control radial force for the endovascular treatment of CVS.…”
Section: Other Instrumentsmentioning
confidence: 99%
“…The most utilized endovascular treatment options are balloon angioplasty and intra-arterial vasodilator (IAV) therapies 4. The recently published VITAL study demonstrated the complementary utility of the NeVa VS device (stent retriever) in mechanical dilatation treatment of severely narrowed vasospastic vessels following aSAH with mean improvement of 36.1% of vessel caliber compared with pre-treatment in 74 vessels in 30 patients 5. Other single-center reports have described the utility of other commercially available stent retrievers for mechanical endovascular dilation of symptomatic vasospasm with encouraging results 6–8.…”
Section: Introductionmentioning
confidence: 99%